And history repeats itself... Fractional tree - Edmundo Capelas de Oliveira (CQD Revista Eletrônica Paulista de Matemática, 2022)
This article aims to present some important points within the evolution of fractional calculus, which today in the field of scientific research has become a field of great relevance with its important contributions to the development of science. It is important to note that this article is a transcription of the lecture given by Professor E. Capelas de Oliveira as the closing lecture of the II Brazilian Congress of Fractional Calculus, which gives a brief explanation of fractional calculus and some of their contributions throughout his career at Unicamp, addressed to its former master and doctoral students. Even more, as the lecture was given in Portuguese, a lot is lost in the transcription to another language.